Heraclitus and the Community of Inquiry (Analytic Teaching, 1996)
Introduction:  Those who look at the title of this paper could ask themselves: again Heraclitus? Again a Greek? Again a philosopher from early history? Why are we looking again at the history of philosophy, and, in this case, at the very beginning of that history? What can Heraclitus give us? What can we obtain from a source so distant in time, space and reality?